Certificateless aggregate signature with efficient verification. Issue 13 (13th November 2014) - Chen, Yu‐Chi; Tso, Raylin; Mambo, Masahiro; Huang, Kaibin; Horng, Gwoboa
Abstract Certificateless public key cryptography (CL‐PKC) is a cryptosystem solving the key escrow problem of identity‐based cryptography. One of the applications of CL‐PKC is certificateless aggregate signature (CLAS) that in practice can be used to efficiently verify concealed data aggregation in wireless sensor networks. CLAS is referred to as an extension of certificateless signature, which in particular performs verification for many signatures efficiently. Therefore, not only plenty of CLAS schemes have been proposed but also the security models of CLAS were introduced in the literature. Recently, some CLAS schemes are extended from specific certificateless signature (CLS) schemes. However, we found that two certificateless signature (CLS) and their corresponding CLAS schemes are not secure. In this paper, we simplify the relation of security definitions of CLS and CLAS. Then, a new CLAS scheme is proposed, which leads to the advantages of both certificateless cryptography and aggregate signature. Moreover, our scheme only depends on constant pairing operations to verify a large number of signatures per time, because pairing is a complicated operation with high cost in computations. Copyright © 2014 John Wiley & Sons, Ltd.